Resolution of chronic lower back pain symptoms through high-intensity therapeutic exercise and motor imagery program: a case-report - Ribas, Jorge (2021)
Nonspecific chronic lower back pain (CLBP) is a difficult to manage clinical condition that is more prevalent in adulthood but also affects adolescents, compromising their well-being and activities of daily living. This case report aimed to describe the clinical evolution of a female adolescent with nonspecific and severe CLBP treated successfully through a combination of high-intensity exercise and motor imagery training.